NANO-DELIVERY SYSTEMS FOR ENHANCING ORAL BIOAVAILABILITY OF DRUGS - ABDELLATIF, MENNA M.; AHMED, SARA MOHAMED; EL-NABARAWI, MOHAMED A.; TEAIMA, MAHMOUD (International Journal of Applied Pharmaceutics, 2023)
The two main issues impacting oral delivery are drug solubility and permeability. The FDA adopted the Biopharmaceutics Classification System (BCS) in 2000. The BCS categorizes drugs into four classes based on their solubility and permeability. For permeability improvement and bioavailability, many experimental systems are utilized. Numerous nanocarrier technologies have recently been utilized to increase drug permeability by employing nanocarrier systems such as lipid vesicles, polymeric and lipid nanoparticles, polymeric micelles, and submicron lipid emulsions. This review proposes innovative nano-delivery systems for permeability augmentation. It focuses on some illustrations of drugs with various nanosystems, how these systems were developed, and how they successfully boost intestinal drug permeability and bioavailability.